2019
DOI: 10.1098/rspb.2019.0582
|View full text |Cite
|
Sign up to set email alerts
|

Loser-effect duration evolves independently of fighting ability

Abstract: Winning or losing contests can impact subsequent competitive behaviour and the duration of these effects can be prolonged. While it is clear effects depend on social and developmental environments, the extent to which they are heritable, and hence evolvable, is less clear and remains untested. Furthermore, theory predicts that winner and loser effects should evolve independently of actual fighting ability, but again tests of this prediction are limited. Here we used artificial selection on replicated beetle po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The loser effect is the consequence of losing an aggressive encounter, while the critical indicator of reversal of the loser effect is elevated aggression (in losers). Interestingly, a recent finding in beetles suggested a separation between fighting ability and the loser effect ( Okada et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The loser effect is the consequence of losing an aggressive encounter, while the critical indicator of reversal of the loser effect is elevated aggression (in losers). Interestingly, a recent finding in beetles suggested a separation between fighting ability and the loser effect ( Okada et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Long-lasting motivational changes enable the animal to avoid similar potentially dangerous or harmful situations in the future (Bateson 1991 ; Elwood et al 2017 ); the greater the noxious stimulus, the more long-lasting the future impact. For instance, individuals suffering injuries during a contest show a loser effect for longer (Hsu et al 2006 ; Briffa & Sneddon 2007 ; Okada et al 2019 ). The experience of shell fracture could resemble a life-threatening predator attack, since once their shell is broken the hermit crabs have no other defence to survive a predation attempt.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, after generation eight of experimental evolution, males from the nine populations (control, male predation, and female predation) were collected. We observed 20 contests per population ( n = 180 in total) in which focal experimental males competed against a male collected from the stock culture using standard methods 39 , 76 . In brief, the stock males were marked with white spots [Mitsubishi Paint-Marker] on their elytra for identification.…”
Section: Methodsmentioning
confidence: 99%
“…To control for the effect of body size on fighting success, males were paired so that the difference in body size between contestants was less than 0.05 mg. Pairs were placed on filter-paper (17 mm diameter) in a plastic container (17 mm diameter, 20 mm high) and allowed to interact (and fight) for 1 h. Previous work has shown that male fights occur in all trials when staged in this manner 76 . Males that pushed opponents and chased them were denoted the winner 76 . Trials were then continuously observed until fight outcomes could be scored.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation